Floral development and vascularization help to explain merism evolution in Paepalanthus (Eriocaulaceae, Poales) - Silva, Arthur de Lima [UNESP]; Trovó, Marcelo; Coan, Alessandra Ike [UNESP] (PeerJ, 2016)
Background. Flowers in Eriocaulaceae, a monocot family that is highly diversified in Brazil, are generally trimerous, but dimerous flowers occur in Paepalanthus and a few other genera. The floral merism in an evolutionary context, however, is unclear. Paepalanthus encompasses significant morphological variation leading to a still unresolved infrageneric classification. Ontogenetic comparative studies of infrageneric groups in Paepalanthus and in Eriocaulaceae are lacking, albeit necessary to establish evolution of characters such as floral merism and their role as putative synapomorphies. Methods. We studied the floral development and vascularization of eight species of Paepalanthus that belong to distinct clades in which dimery occurs, using light and scanning electron microscopies. Results. Floral ontogeny in dimerous Paepalanthus shows lateral sepals emerging simultaneously and late-developing petals. The outer whorl of stamens is absent in all flowers examined here. The inner whorl of stamens becomes functional in staminate flowers and is reduced to staminodes in the pistillate ones. In pistillate flowers, vascular bundles reach the staminodes. Ovary vascularization shows ventral bundles in a commissural position reaching the synascidiate portion of the carpels. Three gynoecial patterns are described for the studied species: (1) gynoecium with a short style, two nectariferous branches and two long stigmatic branches, in most species; (2) gynoecium with a long style, two nectariferous branches and two short stigmatic branches, in P. echinoides; and (3) gynoecium with long style, absent nectariferous branches and two short stigmatic branches, in P. scleranthus. Discussion. Floral development of the studied species corroborates the hypothesis that the sepals of dimerous flowers of Paepalanthus correspond to the lateral sepals of trimerous flowers. The position and vascularization of floral parts also show that, during dimery evolution in Paepalanthus, a flower sector comprising the adaxial median sepal, a lateral petal, a lateral stamen and the adaxial median carpel was lost. In the staminate flower, the outer whorl of staminodes, previously reported by different authors, is correctly described as the apical portion of the petals and the pistillodes are reinterpreted as carpellodes. The occurrence of fused stigmatic branches and protected nectariferous carpellodes substantiates a close relationship between P. sect. Conodiscus and P. subg. Thelxinoë. Free stigmatic branches and exposed carpellodes substantiate a close relationship between P. sect. Diphyomene, P. sect. Eriocaulopsis and P. ser. Dimeri. Furthermore, the loss of nectariferous branches may have occurred later than the fusion of stigmatic branches in the clade that groups P. subg. Thelxinoë and P. sect. Conodiscus.
Keywords: Dimery; Floral anatomy; Floral ontogeny; Monocotyledons; Paepalanthoideae